Behavioral and Social Science Research: A National Resource, Part I - National Research Council (The National Academies Press, 1982)
Behavioral and Social Science Research: A National Resource specifies appropriate criteria for assessing the value, significance, and social utility of basic research in the social sciences. This report identifies illustrative areas of basic research in the social sciences that have developed analytic frameworks of high social utility and describes the development of these frameworks and their utilization. It also identifies illustrative areas of basic research in the social sciences that are likely to be of high value, significance, and/or social utility in the near future, reviews the current state of knowledge in these areas, and indicates research efforts needed to bring these areas to their full potential.
Keywords: Behavioral and Social Sciences

Assisted Resettlement and Community Viability on Louisiana's Gulf Coast: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In 2021, the Gulf Research Program of the National Academies of Sciences, Engineering, and Medicine sponsored a two-year consensus study, Managed Retreat in the U.S. Gulf Coast Region, to examine and make findings and recommendations regarding the unique challenges associated with managed retreat among vulnerable coastal communities in the region. To gather information for the consensus report, the authoring committee convened a series of three public workshops in the Gulf Coast region. The workshops, held in June and July of 2022, focused on policy and practice considerations, research and data needs, and community engagement strategies. This publication summarizes the presentations and discussions of the workshops.
Keywords: Behavioral and Social Sciences

Using Science as Evidence in Public Policy - National Research Council (The National Academies Press, 2012)
Using Science as Evidence in Public Policy encourages scientists to think differently about the use of scientific evidence in policy making. This report investigates why scientific evidence is important to policy making and argues that an extensive body of research on knowledge utilization has not led to any widely accepted explanation of what it means to use science in public policy. Using Science as Evidence in Public Policy identifies the gaps in our understanding and develops a framework for a new field of research to fill those gaps.
Keywords: Behavioral and Social Sciences; Education

Contributions of Land Remote Sensing for Decisions About Food Security and Human Health: Workshop Report - National Research Council (The National Academies Press, 2007)
Land remote sensing: the use of space-based satellite technologies to obtain information on environmental variables such as land-use and land-covering combination with other types of data can provide information on changes in the Earth's surface and atmosphere that are critical for forecasting and responding to human welfare issues, such as disease outbreaks, food shortages, and floods. This book summarizes a workshop on the potential contributions of remotely sensed data to land-use and land-cover change and ways to use physical, biological, temporal, and social characteristics of particular locations to support decisions about human welfare. The discussions focused on human health and food security, two aspects of human welfare in which remotely-sensed environmental conditions play a key role. Examples illustrating the possibilities for applying remote sensing for societal benefit are included throughout the report. As a result of the workshop, three themes were identified that, if fostered, could help realize the potential for the application of land remote sensing to decisions about human welfare: (1) integration of spatial data on environmental conditions derived from remote sensing with socioeconomic data; (2) communication between remote sensing scientists and decision makers to determine effective use of land remote sensing data for human welfare issues; and (3) acquisition and access to long-term environmental data and development of capacity to interpret these data.
Keywords: Behavioral and Social Sciences; Earth Sciences

Methods to Foster Transparency and Reproducibility of Federal Statistics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In 2014 the National Science Foundation (NSF) provided support to the National Academies of Sciences, Engineering, and Medicine for a series of Forums on Open Science in response to a government-wide directive to support increased public access to the results of research funded by the federal government. However, the breadth of the work resulting from the series precluded a focus on any specific topic or discussion about how to improve public access. Thus, the main goal of the Workshop on Transparency and Reproducibility in Federal Statistics was to develop some understanding of what principles and practices are, or would be, supportive of making federal statistics more understandable and reviewable, both by agency staff and the public. This publication summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences

Advancing Antiracism, Diversity, Equity, and Inclusion in STEMM Organizations: Beyond Broadening Participation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Individuals from minoritized racial and ethnic groups continue to face systemic barriers that impede their ability to access, persist, and thrive in science, technology, engineering, mathematics, and medicine (STEMM) higher education and workforce. Without actively dismantling policies and practices that disadvantage people from minoritized groups, STEMM organizations stand to lose much needed talent and innovation as well as the ideas that come from having a diverse workforce. A new report from the Board on Behavioral, Cognitive, and Sensory Sciences examines the backdrop of systemic racism in the United States that has harmed and continues to harm people from minoritized groups, which is critical for understanding the unequal representation in STEMM. The report outlines actions that top leaders and gatekeepers in STEMM organizations, such as presidents and chief executive officers, can take to foster a culture and climate of antiracism, diversity, equity, and inclusion that is genuinely accessible and supportive to all.
Keywords: Behavioral and Social Sciences

Risks and Risk Governance in Shale Gas Development: Summary of Two Workshops - National Research Council (The National Academies Press, 2014)
Natural gas in deep shale formations, which can be developed by hydraulic fracturing and associated technologies (often collectively referred to as "fracking") is dramatically increasing production of natural gas in the United States, where significant gas deposits exist in formations that underlie many states. Major deposits of shale gas exist in many other countries as well. Proponents of shale gas development point to several kinds of benefits, for instance, to local economies and to national "energy independence". Shale gas development has also brought increasing expression of concerns about risks, including to human health, environmental quality, non-energy economic activities in shale regions, and community cohesion. Some of these potential risks are beginning to receive careful evaluation; others are not. Although the risks have not yet been fully characterized or all of them carefully analyzed, governments at all levels are making policy decisions, some of them hard to reverse, about shale gas development and/or how to manage the risks. Risks and Risk Governance in Shale Gas Development is the summary of two workshops convened in May and August 2013 by the National Research Council's Board on Environmental Change and Society to consider and assess claims about the levels and types of risk posed by shale gas development and about the adequacy of existing governance procedures. Participants from engineering, natural, and social scientific communities examined the range of risks and of social and decision-making issues in risk characterization and governance related to gas shale development. Central themes included risk governance in the context of (a) risks that emerge as shale gas development expands, and (b) incomplete or declining regulatory capacity in an era of budgetary stringency. This report summarizes the presentations on risk issues raised in the first workshop, the risk management and governance concepts presented at the second workshop, and the discussions at both workshops.
Keywords: Behavioral and Social Sciences; Energy and Energy Conservation; Environment and Environmental Studies

Trust and Confidence at the Interfaces of the Life Sciences and Society: Does the Public Trust Science? A Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Does the public trust science? Scientists? Scientific organizations? What roles do trust and the lack of trust play in public debates about how science can be used to address such societal concerns as childhood vaccination, cancer screening, and a warming planet? What could happen if social trust in science or scientists faded? These types of questions led the Roundtable on Public Interfaces of the Life Sciences of the National Academies of Sciences, Engineering, and Medicine to convene a 2-day workshop on May 5-6, 2015 on public trust in science.
Keywords: Biology and Life Sciences; Education; Behavioral and Social Sciences

On Being a Scientist: Responsible Conduct in Research, Second Edition - Institute of Medicine; National Academy of Sciences; National Academy of Engineering (The National Academies Press, 1995)
Since the first edition of On Being a Scientist was published in 1989, more than 200,000 copies have been distributed to graduate and undergraduate science students. Now this well-received booklet has been updated to incorporate the important developments in science ethics of the past 6 years and includes updated examples and material from the landmark volume Responsible Science (National Academy Press, 1992). The revision reflects feedback from readers of the original version. In response to graduate students' requests, it offers several case studies in science ethics that pose provocative and realistic scenarios of ethical dilemmas and issues. On Being a Scientist presents penetrating discussions of the social and historical context of science, the allocation of credit for discovery, the scientist's role in society, the issues revolving around publication, and many other aspects of scientific work. The booklet explores the inevitable conflicts that arise when the black and white areas of science meet the gray areas of human values and biases. Written in a conversational style, this booklet will be of great interest to students entering scientific research, their instructors and mentors, and anyone interested in the role of scientific discovery in society.
Keywords: Behavioral and Social Sciences; Policy for Science and Technology; Explore Science; Education